PENGARUH KOMPETENSI PROFESIONAL DAN EFIKASI DIRI DI MODERASI DENGAN KEPEMIMPINANTRANSFORMASIONAL KEPALA SEKOLAH TERHADAP KINERJA GURU - Slamet, Slamet; Sutomo, Yohanes (Jurnal Ilmiah Telaah Manajemen, 2017)
This studyexamined therole ofTransformasional LeadershipModeratingEffects ofTeacher Profesional Competenceand Selfefficay towards Teacher Performance(Case Study TheState Vocational SchoolinPemalang). The specific objectives ofthe studyistoexaminehow therole ofthe Transformasional Leadership effects Teacher Profesional CompetenciesandModeratingEffects ofTeacherSelf-Efficacy towards Teacher PerformanceinPemalang. The usefulness ofthis studyclarify andextendprevious research on theInfluence ofTeacher Profesional CompetenceandSelfEfficacy towardstTeacher Performance. The populationin this study wereteachersatSMKPemalangtotaling148people. Inthis studyusingprimary dataobtainedbyquestionnaire. The research methodusinga computerizedapproachto thestatistical programSPSS(StatisticalPackagefor SocialScience). The methodof dataanalysisusedlinear regressiontotestthe moderating effects The results showedthat the Profesional competenceof teachershasa Negatif and significanteffecton the teacher performance. Self-efficacy hasa positiveand significanteffecton the performanceof teachers. Transformasional Leadeship has apositive and significant impacton the performanceof teachers. Transformasional Leaderhip moderate theinfluence ofteachers' Professional competenceis significant to the performanceof teachers. Transformasional Leadership moderatinginfluence ofself-efficacywassignificant to the performanceof teachers. Keywords: Transformasional leadership,teacher Professional competence, teacherself-efficacy, performanceandmoderation.